2020
DOI: 10.7759/cureus.8124
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Osteoarticular Infective Endocarditis by Methicillin-sensitive Staphylococcus Aureus

Abstract: Al-bayati et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Staphylococcus aureus is a leading cause of human bacterial infection, and the most common site of Staphylococcus aureus infection is the skin[ 13 ]. Skin and soft tissue infections with Staphylococcus remain a dominant cause of bacteraemia and IE[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is a leading cause of human bacterial infection, and the most common site of Staphylococcus aureus infection is the skin[ 13 ]. Skin and soft tissue infections with Staphylococcus remain a dominant cause of bacteraemia and IE[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all described pathologies in the present work, one infection could be the complication of the other which is a pathological behavior frequently observed in S. aureus. In this sense, Albayati et al (2020) have reported that S. aureus skin and soft tissue infections cause an unusual complication of persistent bacteremia which itself leads to complicated endocarditis in addition to an affinity of the involved strain for vertebral osteomyelitis (Al-bayati et al, 2020). Several studies have documented the risk of endocarditis as a complication of bacteremia and have confirmed that it is a serious complication (Bouchiat et al, 2015;Andersen et al, 2020).…”
Section: Invasive Infections Caused By Invasive Infections Caused By ...mentioning
confidence: 99%